Efektivitas Islamic Parenting dalam Membentuk Karakter Anak Usia Dini - Rohmah, Prilia Zulfatur; Daliman (Journal of Psychology and Treatment, 2022)
In the application of the character values ​​of a nation, the active role of an education unit must be able to be responsible for preparing good human resources and be able to face various problems and challenges of life, both locally, regionally, nationally and internationally. In the world of education, it is not enough to only be able to master theories, but also to be willing and able to apply them in social life. In conducting this research, the method used as a reference is to use a descriptive research method through a qualitative approach. Based on the results of research conducted on six parental participants who have elementary school children and apply Islamic parenting strategies in growing a child's character in the Soloraya area, there are five strategies or ways to grow a child's character through Islamic parenting, namely: religious approach, giving positive stimulus, asking others for help, determining punishment, giving rewards (prizes). The application of Islamic parenting provides benefits in growing children's character.